Evidence, policy and practice : Critical perspectives in health and social care - Glasby, Jon (Book collections on Project MUSE., 2011)
This edited book provides a hard-hitting and deliberately provocative overview of the relationship between evidence, policy and practice, how policy is implemented and how research can and should influence the policy process.